Unidirectional trans‐Atlantic gene flow and a mixed spawning area shape the genetic connectivity of Atlantic bluefin tuna - Natalia Díaz‐Arce; Pierre‐Alexandre Gagnaire; David E. Richardson; John F. Walter; Sophie Arnaud‐Haond; Jean‐Marc Fromentin; Deirdre Brophy; Molly Lutcavage; Piero Addis; Francisco Alemany; Robert Allman; Simeon Deguara; et al. (Molecular Ecology, 2024)
The commercially important Atlantic bluefin tuna ( Thunnus thynnus ), a large migratory fish, has experienced notable recovery aided by accurate resource assessment and effective fisheries management efforts. Traditionally, this species has been perceived as consisting of eastern and western populations, spawning respectively in the Mediterranean Sea and the Gulf of Mexico, with mixing occurring throughout the Atlantic. However, recent studies have challenged this assumption by revealing weak genetic differentiation and identifying a previously unknown spawning ground in the Slope Sea used by Atlantic bluefin tuna of uncertain origin. To further understand the current and past population structure and connectivity of Atlantic bluefin tuna, we have assembled a unique dataset including thousands of genome‐wide single‐nucleotide polymorphisms (SNPs) from 500 larvae, young of the year and spawning adult samples covering the three spawning grounds and including individuals of other Thunnus species. Our analyses support two weakly differentiated but demographically connected ancestral populations that interbreed in the Slope Sea. Moreover, we also identified signatures of introgression from albacore ( Thunnus alalunga ) into the Atlantic bluefin tuna genome, exhibiting varied frequencies across spawning areas, indicating strong gene flow from the Mediterranean Sea towards the Slope Sea. We hypothesize that the observed genetic differentiation may be attributed to increased gene flow caused by a recent intensification of westward migration by the eastern population, which could have implications for the genetic diversity and conservation of western populations. Future conservation efforts should consider these findings to address potential genetic homogenization in the species.

Exploitation shifted trophic ecology and habitat preferences of Mediterranean and Black Sea bluefin tuna over centuries - Adam J. Andrews; Christophe Pampoulie; Antonio Di Natale; Piero Addis; Darío Bernal‐Casasola; Veronica Aniceti; Gabriele Carenti; Verónica Gómez‐Fernández; Valerie Chosson; Alice Ughi; Matt Von Tersch; Maria Fontanals‐Coll; et al. (Fish and Fisheries, 2023)
During recent decades, the health of ocean ecosystems and fish populations has been threatened by overexploitation, pollution and anthropogenic‐driven climate change. Due to a lack of long‐term ecological data, we have a poor grasp of the true impact on the diet and habitat use of fishes. This information is vital if we are to recover depleted fish populations and predict their future dynamics. Here, we trace the long‐term diet and habitat use of Atlantic bluefin tuna (BFT), Thunnus thynnus , a species that has had one of the longest and most intense exploitation histories, owing to its tremendous cultural and economic importance. Using carbon, nitrogen and sulphur stable isotope analyses of modern and ancient BFT including 98 archaeological and archival bones from 11 Mediterranean locations ca. 1st century to 1941 CE, we infer a shift to increased pelagic foraging around the 16th century in Mediterranean BFT. This likely reflects the early anthropogenic exploitation of inshore coastal ecosystems, as attested by historical literature sources. Further, we reveal that BFT which migrated to the Black Sea–and that disappeared during a period of intense exploitation and ecosystem changes in the 1980s–represented a unique component, isotopically distinct from BFT of NE Atlantic and Mediterranean locations. These data suggest that anthropogenic activities had the ability to alter the diet and habitat use of fishes in conditions prior to those of recent decades. Consequently, long‐term data provide novel perspectives on when marine ecosystem modification began and the responses of marine populations, with which to guide conservation policy.

Isotopic life‐history signatures are retained in modern and ancient Atlantic bluefin tuna vertebrae - Adam J. Andrews; David Orton; Vedat Onar; Piero Addis; Fausto Tinti; Michelle Alexander (Journal of Fish Biology, 2023)
Isotopic, tagging and diet studies of modern‐day teleosts lacked the ability to contextualise life‐history and trophic dynamics with a historical perspective, when exploitation rates were lower and climatic conditions differed. Isotopic analysis of vertebrae, the most plentiful hard‐part in archaeological and museum collections, can potentially fill this data‐gap. Chemical signatures of habitat and diet use during growth are retained by vertebrae during bone formation. Nonetheless, to fulfil their potential to reveal life‐history and trophic dynamics, we need a better understanding of the time frame recorded by vertebrae, currently lacking due to a poor understanding of fish bone remodelling. To address this issue, the authors serially‐sectioned four vertebral centra of the highly migratory Atlantic bluefin tuna ( Thunnus thynnus ; BFT) captured off Sardinia (Italy) and analysed their isotopic composition. They show how carbon (δ 13 C), nitrogen (δ 15 N) and sulphur (δ 34 S) isotope values can vary significantly across BFT vertebrae growth‐axes, revealing patterning in dietary life histories. Further, they find that similar patterns are revealed through incremental isotopic analysis of inner and outer vertebrae centra samples from 13 archaeological BFT vertebrae dating between the 9th and13th centuries CE. The results indicate that multi‐year foraging signatures are retained in vertebrae and allow for the study of life histories in both modern and paleo‐environments. These novel methods can be extended across teleost taxa owing to their potential to inform management and conservation on how teleost trophic dynamics change over time and what their long‐term environmental, ecological and anthropological drivers are.

Neglected fishery data sources as indicators of pre‐industrial ecological properties of Mediterranean swordfish ( Xiphias gladius , Xiphiidae) - Brian R. MacKenzie; Piero Addis; Pietro Battaglia; Pierpaolo Consoli; Franco Andaloro; Gianluca Sarà; Anders Nielsen; Teresa Romeo (Fish and Fisheries, 2022)
Management of fish populations and ecosystems suffers from data and knowledge gaps, particularly with respect to how humans and nature affect dynamics at multi‐decadal and longer time scales. However, collection of new data which indicates population or ecosystem status is slow and expensive. Here we analyse c. 110 years of neglected fishery data for an overexploited top predator, swordfish, in the Mediterranean Sea. These data are available at scales of high time–space–biological resolution (i.e., sub‐weekly, sub‐regional sea; individual weights) and allow different ecological questions to be addressed than is possible with coarsely scaled data (e.g., annually resolved total catches aggregated over large sea areas). We constructed regional indicators of population status (relative abundance, mean individual size and its variability, migration phenology) covering most of the 20th century, and pre‐dating other population datasets by 50–70 years. The length and duration of these new time series allowed detection of significant multi‐annual/decadal variations in abundance and mean weight not detectable in shorter, more recent time series. These new data and evidence of multi‐annual variability in population variables improve knowledge of Mediterranean swordfish ecology. The findings provide a new basis on which further historical data recovery and analysis of contemporary data can provide new perspectives and opportunities for quantifying vulnerability of populations to exploitation and climate change.

Modelling giant red shrimp larval dispersal in the Sardinian seas: density and connectivity scenarios - Francesco Palmas; Antonio Olita; Piero Addis; Roberto Sorgente; Andrea Sabatini (Fisheries Oceanography, 2017)
The connectivity and three‐dimensional (3D) dispersion of the larvae of giant red shrimp, potentially released from known spawning areas along the Sardinia slope in the western Mediterranean Sea, were assessed using Lagrangian simulations forced by a 3D submesoscale permitting a regional ocean model. Biophysical simulations using the hydrodynamic conditions of the year 2012 were run to track propagules released from known spawning areas during the spawning period (May to September). Passive transport ( PT ) and vertical migration ( VM ) scenarios were tested, each with two possible pelagic larval durations ( PLD s) of 21 or 42 days. Dispersion of propagules in the PT and VM scenarios differed in terms of travelled distance, export out of the domain (larger for VM ), and depth distribution (shallower and bimodal for VM due to the larger variability of encountered currents). Connectivity patterns were investigated among eight release areas, and four predetermined Eco‐Regions, and results showed strong connectivity among the North‐Western ( NW ), Western (W), and Southern (S) regions of Sardinia, whereas the Eastern region was more segregated. Differences in connectivity patterns among scenarios were related mainly to the tendency of greater retention of propagules in the release area for the PT scenarios. This finding, together with existing hypotheses of vertical migration likely occurring during first egg‐larval phases, suggest that the VM scenarios are the most probable of the two hypotheses tested. Strong connectivity between the W and S sides of Sardinia and the relative isolation of the E side could have significant implications for the protection of this important resource.

Effect of two different habitats on spine and gonad colour in the purple sea urchin P aracentrotus lividus - Piero Addis; Davide Moccia; Marco Secci (Marine Ecology, 2015)
This study investigates the effect of different Mediterranean habitats on spine and gonad colouring and gonadal index in the purple sea urchin P aracentrotus lividus (Echinodermata: Echinoidea). Specimens were collected in winter 2012 in P osidonia oceanica meadows and rocky bottom areas at two sites in Southern Sardinia ( I taly, Tyrrhenian Sea). Colorimetric analyses of spines and gonads were conducted with a digital colorimeter using CIELAB colour spaces, which defines the colour in terms of three coordinate values: lightness (L*), redness (a*) and yellowness (b*). Lightness and redness of the spines differed significantly between habitats, whereas colour spaces of the gonads did not. A careful analysis of the gonad index showed it to be significantly affected by habitat, registering higher values in rocky bottom locations. In conclusion, it seems that habitat does affect spine colour but not gonad colour. Spine colour seems to be site‐dependent, whereas the gonad index depends solely on the habitat.

Physiologic Responses to Stress and Changes in Atlantic Bluefin Tuna ( T. thynnus ) Meat Color During Trap Fisheries Capture and Processing in Sardinia (W. Mediterranean) - Piero Addis; Stefano Corrias; Cristian Garau; Marco Secci (Journal of Aquatic Food Product Technology, 2013)

Mycoplasma hominis and Trichomonas vaginalis symbiosis: multiplicity of infection and transmissibility of M. hominis to human cells - Paola Rappelli; Franco Carta; Giuseppe Delogu; Maria Filippa Addis; Daniele Dessì; Piero Cappuccinelli; Pier Luigi Fiori (Archives of Microbiology, 2001)